Prevalence and determinants of cesarean section in a rural tertiary care hospital of Bangladesh - Begum, Fatema; Akter, Saida; Jahan, Arshad; Hoque, Luna Farhana; Aktar, M. Nasrin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cesarean section (CS) stands as the foremost major surgical procedure in contemporary obstetrics. Initially developed primarily to safeguard maternal life during challenging childbirth scenarios, its prevalence has shown a concerning upward trajectory in recent times. The aim of this study was to investigate the prevalence and determinants of Cesarean section deliveries in a rural tertiary care hospital. Methods: This was a retrospective observational study and was conducted in the Department of Obstetrics and Gynaecology of Khwaja Yunus Ali Medical College & Hospital, Sirajganj, Bangladesh during the period from January 2018 to December 2019. Results: Out of a total of 1600 deliveries, 390 (24.4%) were vaginal deliveries, while 1210 (75.6%) were cesarean sections respectively. Majority 94.8% patients were 20-34 years old, 1.8% were less than or equal to 19 years and 3.4% were great than or equal to 35 years old respectively. The majority of cesarean sections, 814 (67.3%), were performed as elective procedures and 396 (32.7%) were performed as emergency procedures respectively. Majority 512 (42.3%) were performed on women who had a history of previous cesarean deliveries, 34 (2.8%) were performed due to non-progression or prolonged labor, 99 (8.2%) were performed due to malpresentation of the baby and 308 (25.5%) were performed at the request of the mother respectively. Conclusions: In conclusion, this retrospective observational study provides valuable insights into the prevalence and determinants of caesarean sections in a rural tertiary care hospital.